THE TRANSLATION OF HYPERBOLIC EXPRESSIONS FROM ENGLISH INTO INDONESIAN : A CASE STUDY IN HOLY BIBLE - Jon Pieter Situmorang; Kevin Dwi Guna Sihite (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research deals with the translation of hyperbolic expressions from English into Indonesian. The researchers used English as a source language and Indonesian as target language. The objective of the study is to find out how English hyperbolic expressions are translated into Indonesian. In conducting this research, the researchers followed these procedures. Firstly, the researchers formulated the problem. Secondly, the researchers built theoretical framework. Thirdly, the researchers collected the data and classified the data based on kinds of hyperbole. Lastly, the researchers examined the data in Indonesian whether hyperbole in English are translated into hyperbole in Indonesian or not. After analyzing the data, the researchers came into a conclusion that English hyperboles are translated into Indonesian in some ways: (i) hyperboles are translated with hyperboles by maintaining the original words in source language (find the proper word equivalents), (ii) hyperboles are t ranslated with hyperboles but the original word in source language are not maintained but are substituted with new word in target language, and (iii) hyperboles are translated non-figuratively. As the result, the writer finds that all of the data are translated into hyperbole.